2012
DOI: 10.1212/wnl.0b013e318266fc51
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing dementia with Lewy bodies by means of diffusion tensor imaging

Abstract: Objective: To investigate patterns of in vivo white matter tract change using diffusion tensor imaging (DTI), we conducted a cross-sectional study of dementia with Lewy bodies (DLB) in comparison with Alzheimer disease (AD) and normal aging. Methods:The study included 106 subjects (35 with DLB, 36 with AD, and 35 elderly controls) who underwent clinical and neuropsychological assessment and diffusion tensor MRI. We used tract-based spatial statistics to investigate patterns of reduced fractional anisotropy (FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
86
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 39 publications
13
86
1
1
Order By: Relevance
“…It shares common clinical and neuropsychological features with other subtypes of dementia such as AD and Parkinson's disease dementia (PDD), but has a distinctive pattern of pathological changes [2,3]. In comparison to AD, DLB has been shown to have less severe atrophy than AD, but with a more diffuse and less focal pattern [4,5], with relatively preserved medial temporal lobes [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It shares common clinical and neuropsychological features with other subtypes of dementia such as AD and Parkinson's disease dementia (PDD), but has a distinctive pattern of pathological changes [2,3]. In comparison to AD, DLB has been shown to have less severe atrophy than AD, but with a more diffuse and less focal pattern [4,5], with relatively preserved medial temporal lobes [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to AD, DLB has been shown to have less severe atrophy than AD, but with a more diffuse and less focal pattern [4,5], with relatively preserved medial temporal lobes [2,[6][7][8]. One of the most notable characteristics of DLB is visuo-spatial deficit, and imaging studies using mostly PET/SPECT in DLB have highlighted the involvement of occipital [9][10][11], temporoparietal [1,3,12] and subcortical areas [13][14][15]. These characteristics of functional rather than structural changes make conventional volumetric MR technique insufficient to fully describe DLB.…”
Section: Introductionmentioning
confidence: 99%
“…WML segmentation is unsatisfactory developed and very often demanding manual outlining is required as well as a FLAIR MR image, where WML is hyper intense, while WM segmentation is readily available from many well known and freely downloadable software packages needing only a 3DT1 MR image which is a common part of a clinical MR protocol. In addition recent focus on diffusion tensor imaging (DTI) in vascular disease [167], amnestic mild cognitive impairment (aMCI) [168], and dementia [169,170,68] strengthens the view that age-related changes in WM plays an important role in the development of dementia. DTI is never the less not suffi-ciently available and at the same time costly making other approaches for WM analysis, like ours, a valuable addition.…”
Section: Discussionmentioning
confidence: 99%
“…Another MR imaging approach showing promising results concerning analysis of white matter integrity is diffusion tensor MRI (DT-MRI) [68]. DT-MRI is an MRI method which is sensitive to the diffusion, or Brownian motion, of water molecules.…”
Section: Mri In Dementiamentioning
confidence: 99%
“…Diffusion tensor imaging has also demonstrated decreased fractional anisotropy (FA) in the precuneus versus both normal controls and AD patients. [49][50][51] Fluorodeoxyglucose positron emission tomography (FDG-PET) demonstrates decreased occipital glucose metabolism, which is helpful in distinguishing among other neurodegenerative diseases, with one study showing 71% decrease in occipital metabolism without much asymmetry. 52 Other studies found temporo-parieto-occipital cortical hypometabolism as well as hypometabolism within the basal ganglia and pulvinar of the thalami.…”
Section: Studiesmentioning
confidence: 99%